2008
DOI: 10.1021/je700368r
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties of Mixed Alkali Bis(trifluoromethylsulfonyl)amides

Abstract: Phase diagrams of binary mixtures of alkali bis(trifluoromethylsulfonyl)amides have been constructed and their eutectic compositions and temperatures have been determined. It has been revealed that the molten salt electrolytes having the melting points in the intermediate temperature range (373 to 473) K are easily formed by simple mixing of two kinds of single alkali bis(trifluoromethylsulfonyl)amides salts. The 1:1 or 3:1 double salt is occasionally formed for some binary systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
127
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 120 publications
(137 citation statements)
references
References 12 publications
8
127
2
Order By: Relevance
“…Therefore, the diffusion of the metallic cations in K[TFSA] melts needs the activation energy more than the dissociation energy with surrounding anions constituting the metal complexes. The value of E a,D is derived from the following Arrhenius rule: [10] where A * is the frequency factor, R the gas constant, and T the absolute temperature. − isomerism was evaluated from the van't Hoff plots from the temperature dependence of the Raman spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the diffusion of the metallic cations in K[TFSA] melts needs the activation energy more than the dissociation energy with surrounding anions constituting the metal complexes. The value of E a,D is derived from the following Arrhenius rule: [10] where A * is the frequency factor, R the gas constant, and T the absolute temperature. − isomerism was evaluated from the van't Hoff plots from the temperature dependence of the Raman spectra.…”
Section: Resultsmentioning
confidence: 99%
“…2a), which is characteristic of a plastic crystal. The T m (118 C) of Li[sTFSI] is much lower than that for LiTFSI (T m ¼ 233 C [62]). It seems that the super-delocalized charge distribution, flexible structure of eSO 2 eNeS(O)]NeSO 2 e, and asymmetric factor of the [sTFSI] À anion play a combinational role in reducing the lattice energy of Li[sTFSI], thus lowering the melting point.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Sodium is abundant in the crust and seawater, showing a relatively low standard redox potential (¹2.71 V vs. SHE). Thus, batteries with low cost and high energy density can be constructed.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 We have already reported that Na[TFSA]-Cs[TFSA] (TFSA = bis(trifluoromethylsulfonyl)amide) and Na[FSA]-K[FSA] (FSA = bis(fluorosulfonyl)amide) ionic liquids are promising electrolytes for sodium secondary batteries operating at an intermediate temperature range (>353 K). [1][2][3][4] However, these salts are solid at room temperature, while electrolytes with lower melting points are more desirable for the construction of batteries for a wide range of practical applications. Recently, we developed a new electrolyte, Na [FSA]-[C 3 C 1 pyrr][FSA] (C 3 C 1 pyrr = N-methyl-N-propylpyrrolidinium), that is a liquid in a wide temperature range, including room temperature.…”
Section: Introductionmentioning
confidence: 99%